Função social da escola e o aspecto educacional do Programa Bolsa Família - Silva, Janaina Pereira da (2014)
This paper bring forward the studies and results of a research about educational view of Brazilian Government Social Programme Support Bolsa Família and a possible reconfiguration about school s social function. This view is a legal consideration to receive this government support, that is to say, the families registered in programme must do the school enrolment of their children and ensure they will have attend school of 85% for children and teenagers 6 to 15 years old or 75% for teenagers with 16 or 17 years old. We intend to investigate whether or not changed the conception of one of school s social function, from the assumption of: the formal and scientific knowledge support for social welfare policies; and research if there changed the schools function from the educational system beyond what are the current school s priorities: the knowledge or enforcement of Bolsa Famíla . To reach this purpose we choose the school with more beneficiaries of this programme on São Paulo City Educational Department of Butantã Hills West Side. We made contact with responsible for school, families, teachers, civil servants that agreed to apply our basis research form. That form was studied from the concept and theories of school social function, the framework was: Teixeira (1971), Fernández (1989), Sacristán e Gómez (1998), Hamilton (2001), Tenti (2007), Young (2007). Between the 22 appliers, 14 think that school is a local only to offer and support the formal and scientific knowledge, 6 understand school as a place of education and as a place of government social programme, and 3 believes school is more a place of government social programme than a place of support knowledge